Curativos produzidos a partir de nanofibras de PVA contendo cloranfenicol - Fraga, Gabriel Nardi (2022)
The electrospinning of polymeric solutions has become an attractive method for application in biomedical areas, such as obtaining dressings. Thus, biocompatible polymers are widely electrospun for tissue engineering, an example is a poly(vinyl alcohol) PVA. However, this polymer has a solubility in water, which is amplified when it is in the form of nanofibers. Therefore, PVA nanofibers need to undergo a crosslinking process in order to improve their stability in water, thus maintaining their morphological structure. In this study, electrospun PVA membranes containing the antibiotic chloramphenicol (CLF) for application as dressings were subjected to two types of crosslinking using citric acid (CA) or glutaraldehyde (GLA). The SEM images showed that it was possible to obtain PVA nanofibers containing the antibiotic chloramphenicol with diameters varying between 600 and 700 nm, with the smallest diameter 593 nm being observed for membranes crosslinked with CA. Crosslinking with citric acid was able to provide better stability of the fibers against aqueous media, maintaining the morphological structures with a loss of 0.7% of the mass after 24h. However, cross-linking with GLA was not able to maintain the fibrous structure, allowing the fibers to coalesce. The improvement in thermal stability promoted by crosslinking was observed in the TGA analysis, as well as in the increase in crystallinity confirmed by the DSC, XRD, and FTIR analyses. The FTIR analysis confirmed the incorporation of the drug in the fibers, while the TGA analysis showed that the CLF delays the thermal degradation of the polymer. The absence of peaks referring to CLF in the X-ray diffractograms and the DSC curves indicate that the drug is possibly in its amorphous state, which improves the drug's solubility making it more bioavailable. The CLF release mechanism shows that the kinetics follows the Weibull model for matrix release systems, presenting a burst release in the first 30 min. The membranes showed hemotoxicity below the established limit (5%), being suitable for application in medical devices, in addition, in the presence of the drug, it promotes antimicrobial activity observed by the disk diffusion assays. Thus, through the results obtained, it was found that these membranes are promising for application in dressings.